Understanding the Mass Trance Phenomenon in Indonesia: Between Traditional Beliefs and Community Mental Health - Hidajat, Lidia Laksana (ANIMA Indonesian Psychological Journal, 2008)
The study on trance phenomenon is hardly ever done, in view of the fact that in Indonesia, trance or known as kesurupan tend to be accepted as a common cultural phenomenon, especially at many areas where traditional and mystical beliefs are profound, and spiritual practices are still carried out. While Indonesia is making a hard effort to build up its nation, and whereas modernization could be seen in many parts of Indonesia, mass trance may perhaps be a paradoxical explanation of every- day social problems. By way of culturally based approaches and ways of thinking of the Indonesian societies, an alternative of social participation and increasing access to economic resources were the determinants that came forward among the research results. Access to supportive relationships, social influence, and opportunities for social engagement which create meaningful roles, resources and op- portunities for contact were among the problems for a better community mental health approach. Studi tentang gejala kesurupan hampir tak pernah dilakukan, mengingat kenyataan bahwa di Indonesia, kesurupan cenderung diterima sebagai gejala budaya biasa, terutama di banyak daerah yang kepercayaan tradisional dan mistiknya menonjol, dan praktik spiritual masih dilakukan. Ketika Indonesia berupaya keras membangun bangsa dan modernisasi terlihat di banyak tempat, kesurupan massal mungkin merupakan penjelasan paradoksikal atas masalah sosial sehari-hari. Melalui pendekatan berbasis budaya dan cara berpikir masyarakat Indonesia, sebuah alternatif partisipasi sosial dan peningkatan akses ke sumber ekonomi merupakan penentu yang muncul di antara hasil penelitian.. Akses ke hubungan yang mendukung, pengaruh sosial, dan kesempatan untuk keterlibatan sosial yang menciptakan peran bermakna, sumber dan kesempatan untuk bersentuhan merupakan bagian masalah untuk mencapai pendekatan kesehatan mental masyarakat yang lebih sehat.